2004
DOI: 10.1186/1471-2202-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caloric deprivation and satiety on sensitivity of the gustatory system

Abstract: Background: Sensitivity of the gustatory system could be modulated by a number of short-term and long-term factors such as body mass, gender, age, local and systemic diseases and pathological processes, excessive alcohol drinking, drug dependence, smoking, composition of oral fluid, state of oral hygiene, consumption of some foods among many others. A few studies have demonstrated the effects of hunger and caloric satiety on sensitivity of the gustatory system in obese humans and animals. The aim of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 15 publications
2
20
0
3
Order By: Relevance
“…Moreover, a possible interaction between tasting profile such as sweet liking or supertasting status with metabolic syndrome has been suggested in adolescence [16] and more recently in the adults [17] . Finally, other investigators have reported that taste sensitivity may be affected by shortterm caloric deprivation in both overweight and lean subjects, with lower thresholds of perception in fasted state than in satiated state [18,19] . Thus, it could be suggested an implication for taste sensitivity also in diet-induced weight loss program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a possible interaction between tasting profile such as sweet liking or supertasting status with metabolic syndrome has been suggested in adolescence [16] and more recently in the adults [17] . Finally, other investigators have reported that taste sensitivity may be affected by shortterm caloric deprivation in both overweight and lean subjects, with lower thresholds of perception in fasted state than in satiated state [18,19] . Thus, it could be suggested an implication for taste sensitivity also in diet-induced weight loss program.…”
Section: Introductionmentioning
confidence: 99%
“…We recognize the lack of sensory capabilities reassessment at the end of the follow-up as a study limitation as we cannot exclude a modification of taste acuity during the program itself. Despite conflicting reports are available on this issue [32] , it seems likely that acute fasting (14-16-h-long) results in lower sensory thresholds [18,19] . It should be noted that we performed our study postabsorptively (14-16 h after last meal), in physiologic state.…”
mentioning
confidence: 99%
“…O estímulo da boca toda permite amplo contato do estímulo com os botões gustativos presentes nas papilas gustativas localizadas na superfície da língua e na mucosa do palato, e em menor número em áreas da garganta (MEILGAARD et al, 1999), sendo considerado mais adequado fisiologicamente e menos cansativo (ZVEREV, 2004).…”
Section: Estímulo Da Boca Todaunclassified
“…O tempo de permanência da solução na boca antes de ser deglutida ou descartada foi relatado somente por dois estudos (ANTONELLO et al, 2007;SPRITZER, 1985), sendo ambos de 10 s. As amostras foram desprezadas em 27,3% dos artigos (ELLEGARD et al, 2007a;MONNEUSE et al, 2008;ZVEREV et al, 2004;PASQUET et al, 2002;MOJET et al, 2001; MIDDLETON; ALLMAN-FARINELLI, 1999) e deglutidas em 18,2% (STEWART-KNOX et al, 2008;GUDZIOL;HUMMEL, 2007;McDAID et al, 2007;OKORO et al, 2002); note-se, porém, que 54,5% não informaram. Quanto à duração do intervalo entre as soluções diferentes, em dois estudos (9,1%), foi de 30 s (ANTONELLO et al, 2007;SPRITZER, 1985); em um estudo (4,5%), de 3 min (WATANABE et al, 2008), e a maioria deles (86,4%) não relatou.…”
Section: Aspectos Gerais Dos Artigos Para Avaliação Sensorialunclassified
See 1 more Smart Citation